Using Slick Write to Improve Writing Skills in EFL Classrooms - Sinar, T. Silvana; Weny, Krisna; Zein, Mutiara; Harefa, Yulianus (TALENTA, 2025)
Slick Write has emerged as a potential solution for improving writing teaching via real-time feedback and automated evaluation. Although current studies have investigated Slick Write's efficacy in facilitating writing tasks, there is a paucity of research on its incorporation within a systematic, pedagogically robust writing instruction framework. This study seeks to assess the efficacy of integrating Slick Write into a holistic writing teaching framework and its influence on enhancing students' academic writing abilities. This study utilized a descriptive research methodology and involved 20 junior high school students from grades 7 to 9 at a private institution in Medan, Indonesia. Writing assessments were conducted before and during the adoption of the Slick Write-integrated approach. The written outputs of students were evaluated utilizing the diagnostic elements of Slick Write, which included an analysis of pronouns, adverbs, function words, sentence and paragraph lengths, passive voice metrics, and prepositional phrase indices. The data were evaluated descriptively to identify patterns of improvement and trends in student performance. The results indicate that Slick Write substantially aids students in the writing process by facilitating the generation, organization, and refinement of their ideas with more independence. The students demonstrated enhanced understanding of linguistic mechanics and word choice. This study introduces a unique Slick Write-integrated educational framework that enhances autonomous learning while complementing instructor feedback. These findings drive home the importance of integrating technological tools such as Slick Write into writing pedagogy to improve writing outcomes and foster learner-centered instruction in higher education.